Las vecinas de Abu Musa : narrativa - Tawfīq, Aḥmad, 1943- (Narrativa (Editorial Verbum), 2014)
In fourteenth-century Morocco, Shamah works as a servant in the house of Chief Judge Ibn al-Hafid. She is a favorite of the judge's senior wife, Al-Tahirah, who takes the beautiful young woman under her wing. Thus, Shamah becomes quite accomplished in many things, such as household management, literary and legal matters, and politesse. Those skills, along with her physical beauty, garner her a surprise marriage proposal from Supreme Judge Abu Salim al Jawra'i. The wedding is arranged posthaste.